2020
DOI: 10.1158/1078-0432.ccr-19-1351
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EZH2 Enhances Antigen Presentation, Antitumor Immunity, and Circumvents Anti–PD-1 Resistance in Head and Neck Cancer

Abstract: Purpose: Anti-programmed death-1 (PD-1) receptor-based therapeutics improve survival in patients with recurrent head and neck squamous cell carcinoma (HNSCC), but many do not benefit due to a low response rate. Herein, we identified EZH2 as a therapeutic target that enhanced tumor cell antigen presentation and subsequently sensitized resistant tumors to anti-PD-1 therapy.Experimental Design: EZH2 regulation of antigen presentation was defined using EZH2 inhibitors (GSK126 and EPZ6438) in human and mouse HNSCC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(126 citation statements)
references
References 41 publications
5
120
0
1
Order By: Relevance
“…Tazemetostat, an EZH2 inhibitor, has been approved for treating epithelioid sarcoma, and it is the first EZH2 inhibitor approved by FDA [47]. Other EZH2 inhibitor, GSK343 and GSK236, were also reported to inhibit tumor progression in various cancer, such as glioblastoma [48], head and neck cancer, [49] and breast cancer [50]. Our in vitro study confirmed the regulatory mechanism of miR-33a/EZH2 cascade in TNBC progression, thus, more investigation of the effects of miR-33a and EZH2 on tumor growth and metastasis in vivo is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Tazemetostat, an EZH2 inhibitor, has been approved for treating epithelioid sarcoma, and it is the first EZH2 inhibitor approved by FDA [47]. Other EZH2 inhibitor, GSK343 and GSK236, were also reported to inhibit tumor progression in various cancer, such as glioblastoma [48], head and neck cancer, [49] and breast cancer [50]. Our in vitro study confirmed the regulatory mechanism of miR-33a/EZH2 cascade in TNBC progression, thus, more investigation of the effects of miR-33a and EZH2 on tumor growth and metastasis in vivo is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 1/ 2, multi-center, open-label study (NCT03525795), the strategy of CPI-1205 plus ipilimumab is under evaluation in patients with advanced solid tumors. A recent study revealed the inhibition of EZH2 could enhance cancer cell antigen presentation in head and neck squamous cell carcinoma (HNSCC) and avoid anti-PD-1 resistance [95].…”
Section: Ezh2 Inhibitors Combined With Other Therapy Methodsmentioning
confidence: 99%
“…Thus, EZH2 is a relevant target in cancer therapies attempting to improve T cell recruitment into the TME. Specifically, expression of CXCR3 on T cells, which binds to ligands CXCL9/CXCL10, was highlighted in recent findings to be critical for drawing T cells into the TME and informs the design of future therapeutics with a primary aim of improving T cell recruitment (49,(52)(53)(54). Furthermore, the effect of EZH2 inhibition on destabilizing the regulatory T cell lineage is another primary consideration that was demonstrated to impact antitumor immunity (48,55).…”
Section: Regulation Of Cd8+ T Cells During Cancermentioning
confidence: 99%